2005
DOI: 10.1158/1078-0432.ccr-04-1101
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Excision Repair Gene Polymorphisms and Recurrence after Treatment for Superficial Bladder Cancer

Abstract: Purpose: Interindividual differences in DNA repair capacity not only modify individual susceptibility to carcinogenesis, but also affect individual response to cancer treatment. Nucleotide excision repair (NER) is one of the major DNA repair pathways in mammalian cells involved in the removal of a wide variety of DNA lesions. Polymorphisms in NER genes may influence DNA repair capacity and affect clinical outcome of bladder cancer treatment. Experimental Design: To test the influence of NER gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 27 publications
1
68
1
Order By: Relevance
“…Concerning bladder cancer, Gu et al (2005) showed that the NER gene Sak et al (2005) indicated that high expression levels of APE1 and XRCC1 are associated with improved cancer-specific survival following radical radiotherapy in muscle-invasive bladder cancer. However, reports on the associations between DNA repair gene polymorphisms and clinical response or prognosis in muscle-invasive bladder cancer patients treated with chemotherapy or radiotherapy are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning bladder cancer, Gu et al (2005) showed that the NER gene Sak et al (2005) indicated that high expression levels of APE1 and XRCC1 are associated with improved cancer-specific survival following radical radiotherapy in muscle-invasive bladder cancer. However, reports on the associations between DNA repair gene polymorphisms and clinical response or prognosis in muscle-invasive bladder cancer patients treated with chemotherapy or radiotherapy are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Sak et al (2005) stated that one possible explanation is that the reduced expression of XRCC1 and APE1 merely reflects the poorly differentiated nature of tumour cells in more aggressive tumours, and that cells from aggressive tumours with extensive genomic instability could contain chromosomal aberrations that result in the failure of transcription of genes, including DNA repair genes, thus resulting in lower protein expression of the gene products. Gu et al (2005) analysed the association between the total number of variant alleles in eight NER genes and the recurrence of superficial bladder cancer. They emphasised that because the prognosis of cancer patients likely involves multistep, multigenic pathways, it is unlikely that any one single genetic polymorphism would have a dramatic effect on clinical outcome, and that it is important to take a pathway-based analysis of multiple polymorphic genes (Gu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotyping for the Lys939Gln and Ala499Val polymorphisms were performed as described previously using the TaqMan assay [23]. PCR-RFLP was conducted to genotype the PAT polymorphism according to a previous protocol with minor modifications [24].…”
Section: Genotypingmentioning
confidence: 99%
“…Hundreds of polymorphisms in DNA repair genes have been identified and some of them have been consistently associated with cancer susceptibility [Hung et al, 2005;Spitz et al, 2003;Ribas et al, 2006]. For example, the OGG1 p.S326C and the XRCC1 p.R194W have been shown to be associated with an increased risk of various types of human cancer; while the BRCA2 p.N372H was reported to be more specifically associated with an increased risk of breast cancer [Goode et al, 2002;Gu et al, 2005]. A number of SNPs were also identified in the ERCC6 gene and a recent study reported that the ERCC6 p.M1097V had a significant impact on bladder cancer recurrence [Gu et al, 2005].…”
Section: Ercc6 (Also Known As Cockayne Syndrome [Cs] Complementation mentioning
confidence: 99%